Imputing Rainfall Data for Flood Simulation in Citarum River, West Java - Muhammad Yoga Pratama; Stevanus Nalendra Jati; Muhammad Rendana (Program Pascasarjana Universitas Sriwijaya, 2023)
The central role of the Citarum River as a buffer to meet the needs of agricultural irrigation, industrial activities, and raw water in the six surrounding districts, including 80% of the population of Jakarta, has experienced a decline in conditions from up-downstream. That way, a lot of data is available regarding the adaptation of floods, drought, and other water source functions for an integrated concept for Citarum. The focus of the study is in the Central Citarum Zone by using 5 and 10 years of rainfall intensity (time series), actualizing the runoff coefficient, Intensity Duration Frequency (IDF) modeling to the formulation of the peak runoff discharge. This achievement is realized by applying Gumbel's Method and Mononobe's Equation and optimizing the 2D HEC-RAS software. Experimental data from 2010 to 2019 indicated that November was the highest rainfall of 448.07 mm/hour, while the lowest was in July with a value of 52.50 mm/hour. The simulation results show an increase in flow rate up to 11%, which means it affects the river's capacity to accommodate the overflow load. Furthermore, this simulation is equipped with a map of the flood-affected areas with a peak discharge scenario in November.